Dog Disease Expert System Using Certainty Factor Method - Marlinda, Linda; Widiyawati, Widiyawati; Indrarti, Wahyu; Widiastuti, Reni (Politeknik Ganesha Medan, 2020)
Many animal keepers at home who do not know the disease contained in the animal's body. Especially for dogs, the lack of information begins to provide care, hygiene, vaccinations for the health of pet dogs and sickles that will be caused by dogs to their owners. Expert systems can provide solutions to the lack of information obtained by pet dog owners, especially dogs. With this expert system, the owner can know the dog's disease and realize the right prevention in treatment. In this paper 25, physical symptoms of the disease are used and found 8 types of common dog diseases. Five options are given to answer the calculation question using each method: no, quite sure, sure enough, certain, and certainty sure. Accuracy Analysis of each method is tested by assessing the results of each analysis method based on user feedback. The results of this study are the application of an expert system that can diagnose dogs using herbal medicines from plants. The purpose of this study is to implement the certainty factor method in the diagnosis system of canine diseases that can provide space in providing value confidence in knowledge. The conclusion in this study will show some questions as indicators of the characteristics of canine disease, until the final question. The conclusion of the study using the certainty factor method will show the characteristics of the disease in dogs. By being obtained from Rabies (0.9) with easy to get angry refuse nomal food; Hepatitis (0,9) with swelling of the liver occurs; Distemser (0,8) with stomach part blister and festering discharge from the eye; canine parvorius (0,8) with loss of appetite and poop there is blood, herpesvirus (0,8) with often roared and complaints, papilomatosis (0,9) with Smelly dog breath, and leptospirosis (0,7) with complaints, and dirofilaria immitis (0,9) with Unstable body temperature